Extracorporeal Membrane Oxygenation Support in COVID-19 Patients: A Propensity Score Analysis. Issue 12 (9th November 2022) - Abramov, Alexey; Su, Irene; Agerstrand, Cara; Flatley, Meaghan; Dubois, Richard; Feldhaus, Danielle; Stanifer, Bryan P.; Sonett, Joshua; Brodie, Daniel; Lemaitre, Philippe
Abstract : Revised guidelines clarify indications for extracorporeal membrane oxygenation (ECMO) support in Coronavirus disease 2019 (COVID-19) patients with acute respiratory distress syndrome (ARDS). Limited data exist to compare clinical outcomes of COVID-19 ARDS patients to non-COVID-19-related ARDS patients when supported with ECMO. An observational propensity-matched study was performed to compare clinical and ECMO-related complications between COVID-19-related ARDS patients (COVID) and non-COVID-19-related ARDS (Control). COVID- patients cannulated from March 1st, 2020, through June 1st, 2021, were included and matched to patients from the historical cohort at our center from 2012 to 2020 based on age, body mass index (BMI), acute physiology and chronic health evaluation (APACHE) II score, and duration ECMO run. The primary outcome was complications during ECMO therapy. A total of 56 patients were propensity matched 1:1 with a mean age of 40.9 years, BMI 32.1 kg/m2, APACHE II score of 26.6, and duration of ECMO support of 22.6 days. In total 18 COVID-19 patients were observed to have more major bleeding complications (18 vs. 9, p = 0.03). Although not statistically significant, they also had more strokes (6 vs. 3) and required more chest tubes (13 vs. 8). Inpatient mortality was not different. ECMO support in COVID-19 patients is associated with more major bleeding complications, strokes, and chest tube placements. The use of ECMO in patients with COVID-19-related ARDS appears to be associated with an increased risk of complications.